Effect of Manures and Fertilizers on Growth and Seedling Quality Indices of the Pterocarpus santallnus (Linn.F) Seedlings - Sankanur, Mahantappa; Somashekharaiah, S. L.; Venkateim, L.; Ganigerand, Basavaraj S.; Shivanna, H. (Indian Forester, 2011)
Among the twelve different treatments, treatment with poultry manure at 33 g per seedling (T8) showed significantly higher seedling height, collar diameter, number of leaves, and dry weight of leaf, shoot, root and total dry weight at 240 days after planting the values for which were 42.50 cm, 4.92 mm, 18.45, 1.38 g, 0.99 g, 1.86 g and 4.23 g, respectively with absolute growth rate (0.017 g/day), sturdiness quotient (8.62) and Dickson’s quality index (0.43) when compared to the initial dry weight ofleaf, shoot, root and total initial dry weight 0.01 g, 0.06 g, 0.09 g and 0.16 g, respectively. It was followed by treatment with Phospho bacteria at 5 g per seedling (T5) which showed seedling growth attributes viz., 41.00 cm seedling height, 3.28 mm collar diameter, 12.51 number of leaves, and dry weight of leaf (0.29 g), shoot (0.83 g), root (2.09 g) and total dry weight (3.19 g) at 240 days after planting with 0.013 g/dayof absolute growth rate, 17.70 of sturdiness quotient and 0.18 of Dickson’s quality index, when compared to the initial dry weight of leaf, shoot, root and total initial dry weight 0.02 g, 0.06 g, 0.08 g and 0.16 g, respectively.